Peran Pengetahuan Awal Guru dalam Mempromosikan Strategi Pembelajaran Bahasa Inggris di Sekolah Dasar - Suciana Wijirahayu (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2017)
This case study is about the primary school teachers’ prior knowledge that influence their beliefs about English as a Foreign Language (EFL) Learning Strategies reflected in their actual classroom practices. There were two senior Indonesian teachers who has more than 10 years teaching experience participated in this research. One of the teacher was teaching in state primary school and the other was teaching in an international primary school in Jakarta. The result of the analysis from participants’ responses to the questionnaire, video-recorded classroom observations and interviews were presented qualitatively in the findings section. The results showed that primary teachers beliefs about EFL Learning strategies were uniquely reflected in their classroom practices suitable to their experience in acquiring and applying Language Learning Strategies (LLSs) in learning English.